Ego dan Emosi Tokoh Ayah dan Anak dalam Novel Seribu Wajah Ayah Karya Nurun Ala: Tinjauan Psikologi Sastra - Dilma, Thesya Ramadhani (Jurnal Ceteris Paribus, 2025)
This study examines the ego and emotions of the father and child characters in the novel "Seribu Wajah Ayah" by Azhar Nurun Ala. Its aim is to describe the psychological issues of the characters through their ego and emotions. To achieve the results of the study, the theory applied is the theory of literary psychology from Sigmund Freud, which includes the structure of personality and the classification of emotions. Sigmund Freud divides the structure of personality into the id, ego, and superego. Freud views the psychological aspect as desires emerging from within the character. The operation of the id is characterized by desires that seek pleasure and avoid discomfort, which are determined by the id and the superego, as well as the superego that weighs the morality of actions taken. The classification of emotions in Freudian psychology is determined by the attitudes of the personality structure. Beyond the structure of personality, the classification of emotions such as guilt, shame, sadness, hate, and love are also found in the father character and the character referred to as “You”.